FUNGSI SOSIALISASI KELUARGA DAN MASYARAKAT DALAM UPAYA MENCEGAH TAWURAN ANTARPELAJAR - Listari, Lasmida (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Brawls between students are a very worrying problem for parents, schools, and the community. The brawl has resulted in many victims, both minor and severe injuries, even to the point of death from being hit by sharp weapons. The incident of brawls between students, of course, also disturbed the peace of the general public. Unfortunately, Indonesia has to lose the young generation to succeed in the nation's struggle in an unexpected event. This article aims to determine the function of family socialization and the role of society as social control in an effort to prevent brawls between students. Through the socialization process in children, parents can instill mutual respect for differences, tolerance, cooperation, fairness to one another, and respecting the rights of others, as well as an understanding of the joint obligations of other community members to create a calm, peaceful, and peaceful life. Peaceful and conducive. This effort can prevent teenagers from doing evil deeds such as brawls between students. Society as social control is needed as an element to avoid brawls between students. The community must instill positive values and be supported by mutually agreed rules to prevent juvenile delinquency. A morally conducive society can teach children and young people how to behave, respect differences, respect the rights of others, and carry out their obligations as members of society